Development of Genially Based Learning Media based on Computational Chemistry on The Subject of Chemical Bonding of 11th Grade High School - Devi Patricia Hutagalung; Dinda Suci Ramadhani; Asep Wahyu Nugraha (Universitas Pendidikan Mandalika, 2026)
This study aims to develop and assess the feasibility level of Genially-based interactive learning media that integrates computational chemistry into chemical bonding materials. The media is designed to be able to display a more concrete visualization of molecular structures, so that it can help students understand abstract concepts. This research is included in the type of Research and Development (R&D) with reference to the ADDIE development model. The instruments used include media validation sheets and material validation sheets that are prepared based on the standards of the National Education Standards Agency (BSNP) and assessed by experts, as well as questionnaires to find out student responses. The results of the needs analysis at SMA Negeri 13 Medan show that the use of technology by teachers in learning is still not optimal, so students tend to feel less interested and have difficulty understanding the material. Based on these conditions, Genially learning media based on computational chemistry on chemical bonding materials was developed as a solution to support students' learning needs. The validation results showed that the developed media obtained an average feasibility percentage of 92% from media experts and 89% from material experts. Meanwhile, student response to this media reached an average of 87%. The final product of this research is in the form of interactive digital learning media. Thus, it can be concluded that Genially's learning media based on computational chemistry on chemical bonding materials is included in the category of being very feasible to be used in the learning process.